Flowshop scheduling using artificial bee colony (ABC) algorithm with varying onlooker bees approaches - Mohd Pauzi, Nur Fazlinda (2015)
The common objectives in permutation flowshop scheduling problem are to minimize the total completion time or formally called as makespan and tardiness. Artificial Bee Colony (ABC) algorithm is one of the methods used to solve the flowshop scheduling problem but only a few researches have been found using this method in this area. Therefore, ABC algorithm is proposed to solve the flowshop scheduling problem in this research. The main objective of this research is to develop a computer program with capability of manipulating the onlooker bee approaches in ABC Algorithm for solving flowshop scheduling problem. The research also analyzes the performance of the ABC algorithm using three different onlooker bee approaches. A simulation computer program was developed using Visual Basic Editor in Microsoft excel 2007. In this simulation, onlooker bees as the important bee make decision to choose the specific method. The performance of the ABC algorithm was evaluated through three different onlooker approaches i.e. method 3+0+0 (three onlooker bees are dedicated to the best employee bee), method 2+1+0 (two onlooker bees are dedicated to the best employee bee and one onlooker bee is dedicated to second best employee bee) and method 1+1+1 (one onlooker bee is dedicated to each employee bee). All the average percentage makespan difference from three onlooker approaches was compared and the lowest average percentage makespan difference was selected as the best method. The simulation results indicated that method 2+1+0 produces best result at low iterations of 102 and below. At high iterations of 204 and above, method 3+0+0 dominates the best performance. Based on this finding, the selection of the best method can be decided based on the iteration time available. If iteration available is long, method 3+0+0 is more appropriate, otherwise method 2+1+0 is the best choice. The findings from this research can be used by system developer or computer programmer to search the optimum sequence during the manufacturing process and improve the flowshop scheduling.